1977
DOI: 10.1021/bi00625a017
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance and chemical modification studies of bovine erythrocyte superoxide dismutase: evidence for zinc-promoted organization of the active site structure

Abstract: Nuclear magnetic resonance (NMR) spectroscopy of the exchangeable protons, tentatively assigned as histidine resonances, of bovine erythrocyte superoxide dismutase in H2O has been found to be a powerful method to study the active site of the enzyme. This technique has been employed in conjunction with chemical modification of the histidine residues using diethylpyrocarbonate (DEP) to show that zinc alone organizes the active site structure. All eight histidines per subunit of apoenzyme react with DEP. The acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 30 publications
6
48
0
Order By: Relevance
“…This information supplements the NMR studies of Cu2,Zn2-SOD and apo-SOD (9,14,24), which only revealed considerable differences in the active site region, and the ultracentrifugation studies of yeast apo-SOD (l 0) which showed a Iog(kot) decrease of the sedimentation coefficient from 3.0 S to 2.5 S upon metal removal, suggesting a general loosening of the protein structure. This is consistent with the observation for bovine apo-SOD, that this protein denatures at a temperature 45 ~ lower than the holo-enzyme (23).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This information supplements the NMR studies of Cu2,Zn2-SOD and apo-SOD (9,14,24), which only revealed considerable differences in the active site region, and the ultracentrifugation studies of yeast apo-SOD (l 0) which showed a Iog(kot) decrease of the sedimentation coefficient from 3.0 S to 2.5 S upon metal removal, suggesting a general loosening of the protein structure. This is consistent with the observation for bovine apo-SOD, that this protein denatures at a temperature 45 ~ lower than the holo-enzyme (23).…”
Section: Discussionsupporting
confidence: 65%
“…reduced (15), whereas zinc is believed to be responsible for correct conformation around the active site (9,24).…”
Section: Introductionmentioning
confidence: 99%
“…For example, binding of zinc ions to the zinc site of the apoprotein causes the protein to adopt a native-like structure, even in the absence of Cu2+ (38), and to increase the overall stability of the protein (36). In addition, removal of zinc ions from WT CuZnSOD to form the zinc-free derivative, Cu"ESOD, causes the SOD activity to become pH dependent (32).…”
Section: Discussionmentioning
confidence: 99%
“…DEPC can also react with other nucleophilic residues including sulfhydryl, arginyl, and tyrosyl residues, as well as with ␣-and ⑀-amino groups (40). However, in contrast to arginine, tyrosine, and amino acids with sulfhydryl side chains, the imidazole ring of histidine is known as a copper binding site, and many studies have demonstrated that metal coordination to histidine residues of peptides or proteins protects these amino acids from DEPC modification (41)(42)(43)(44). Since DEPC-modified histidines increase in mass of 72.06 Da for each mono-carbethoxylation of the pyrrole type of nitrogen in the imidazole ring in exposed residues (di-substituted adducts are only formed at high DEPC concentrations; not presented), resulting adducts can be detected and enumerated by MALDI-MS analysis (45)(46)(47).…”
Section: Metal-protein Binding and Neurodegenerative Disease-mentioning
confidence: 99%